2020
DOI: 10.1111/epi.16589
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish model of posttraumatic epilepsy

Abstract: Objective: Posttraumatic epilepsy (PTE) is defined as recurrent and unprovoked seizures occurring >1 week after traumatic brain injury (TBI). Animal studies of PTE are lengthy and expensive. In this study, we developed a cost-effective PTE animal model using zebrafish to bridge the gap between in vitro studies and low-throughput animal studies. Methods: We used two different sets of parameters (G1 and G2) to induce closedhead TBI in adult zebrafish using pulsed high-intensity focused ultrasound. Injured fish a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Zebrafish larvae are mostly used as a model for epilepsy and seizures due to several advantages, such as high fecundity, leading to numerous fast-developing embryos ex utero allowing researchers to perform easy follow-ups of development and genetic manipulations; possibility for high-throughput analyses using larvae, where each can fit in one well of a 96-well plate; minimal ethical regulations; and relatively low costs for maintenance and housekeeping [121]. However, adult zebrafish are sometimes preferred due to a higher developed neural system, easier handling and certain parameters that sometimes cannot be observed in larvae, e.g., distinct seizure stages [128,129].…”
Section: Measurement Of Seizures In Zebrafishmentioning
confidence: 99%
“…Zebrafish larvae are mostly used as a model for epilepsy and seizures due to several advantages, such as high fecundity, leading to numerous fast-developing embryos ex utero allowing researchers to perform easy follow-ups of development and genetic manipulations; possibility for high-throughput analyses using larvae, where each can fit in one well of a 96-well plate; minimal ethical regulations; and relatively low costs for maintenance and housekeeping [121]. However, adult zebrafish are sometimes preferred due to a higher developed neural system, easier handling and certain parameters that sometimes cannot be observed in larvae, e.g., distinct seizure stages [128,129].…”
Section: Measurement Of Seizures In Zebrafishmentioning
confidence: 99%
“…A recent study demonstrated that brain trauma can induce epileptogenesis and seizures associated with inflammation and blood-brain barrier dysfunction in zebrafish, which resembles pathophysiological processes in human posttraumatic epilepsy [92]. Additionally, the cerebral vasculature of zebrafish is morphologically and physiologically similar to humans and can readily be genetically manipulated [93].…”
Section: Zebrafish Models Of Epilepsymentioning
confidence: 99%
“…Recurrent administration of pilocarpine (Paudel et al, 2020) or pentylenetetrazole (PTZ) (Duy et al, 2017) does not induce recurrent spontaneous seizures. However, we recently modeled post-traumatic epilepsy (Cho et al, 2020b), which is the first adult zebrafish model that exhibits spontaneous seizures. This model also demonstrates disruption of the blood-brain barrier, increased markers of inflammation, and alterations in tau phosphorylation mTOR signaling, mechanisms relevant to epileptogenesis that cannot be as easily studied in larvae.…”
Section: Morphological Changes From Larva To Adultmentioning
confidence: 99%
“…Each non-drug induced epilepsy model can show different types of seizure behaviors. An adult post-traumatic epilepsy model shows reduced motor behavior with spontaneous myoclonic and generalized tonic-clonic seizures (Cho et al, 2020b). SCN1A mutant larvae exhibit increased swim activity with whole-body convulsions and rapid undirected movements (Baraban et al, 2013).…”
Section: Seizure Phenotyping Paradigmsmentioning
confidence: 99%